Oxytocin massage enhanced breast milk production in post-partum women - Widia, Lidia; Meihartati, Tuti (Majalah Obstetri & Ginekologi, 2017)
Objectives: To evaluate the effect of oxytocin massage on breast milk production and maternal comfort in postpartum women. Materials and Methods: This analytical cross-sectional study utilized primary data collected through a structured questionnaire. A total of 36 postpartum mothers were recruited using a non-probability sampling technique. Data were analyzed using the Chi-square test with a significance level set at 0.05. Results: The Chi-square analysis demonstrated a significant association between oxytocin massage and breast milk production (p = 0.001). Conclusion: Oxytocin massage significantly improved breast milk production among postpartum mothers at the Batulicin 1 Public Health Center, Tanah Bumbu District, South Kalimantan.